Prevalence of Salmonella, Shigella, and parasites in food handlers at Bahir Dar university, Ethiopia - Tarik Yenew Tessema; Tewachew Awoke; Zewdu Bishaw Aynalem; Bazezew Asfaw Guadie; Biruk Legese; Rima D. Shrestha; Daniel Mekonnen (BMC Infectious Diseases)
Abstract Background Gastrointestinal diseases caused by Salmonella, Shigella, and intestinal parasites remain major public health problems in developing countries such as in East Africa. Food handlers with poor hygiene practices contribute significantly to the spread. This study aimed to determine the magnitude of Salmonella, Shigella, and intestinal parasites, identify associated factors, and determine the antibiotic susceptibility profiles of bacterial isolates among food handlers in Bahir Dar University students’ cafeterias, Northwest Ethiopia. Methods A facility-based cross-sectional study was conducted on 404 food handlers from April 27 to June 24, 2023. Participants were recruited using computer-generated simple random sampling. Self-administered questionnaires and observation checklists were used to collect data. Stool specimens were transported in Cary-Blair medium, enriched in Selenite F broth, sub-cultured on xylose lysine deoxycholate agar for isolation of Salmonella and Shigella, and identified by biochemical tests. Intestinal parasites were identified through wet mount. Antibiotic susceptibility testing was done using the Kirby-Baur method based on CLSI guidelines. Data were entered into Epi-Data 3.1, analyzed with SPSS 25, and logistic regression was employed to assess associations between variables. Results From the total 404 food handlers, the prevalence of Salmonella, Shigella, and intestinal parasites was 2.2%, 0.7%, and 28.2%, respectively. Entamoeba histolytica/dispar was the predominant parasite detected. All Salmonella and Shigella isolates were susceptible to ciprofloxacin and chloramphenicol. Salmonella, 8/9 (88.9%) and Shigella, 3/3 (100%) were ampicillin resistant. Fingernail status (AOR = 10.36, 95% CI: 5.64, 19.03, p-value: <0.001), medical checkups (AOR = 3.65, 95% CI: 1.47, 9.07, p-value: 0.005), hand washing before meals (AOR = 3.06, 95% CI: 1.09, 8.63, p-value: 0.034) and after using toilet (AOR = 3.21, 95% CI: 1.40, 7.33, p-value: 0.006) were significantly associated with intestinal infections. Conclusion Regular screening, along with strict adherence to hygiene practices such as proper hand washing and trimmed fingernails, is essential to reduce the risk of contamination and prevent the transmission of Salmonella, Shigella, and intestinal parasites.